The catcher was a spy [videorecording (DVD)] - Lewin, Ben, 1946-; Rudd, Paul; Strong, Mark, 1963-; Miller, Sienna, 1981-; Dawidoff, Nicholas (Paramount, 2018)
Dramatizes the life of Moe Berg, a baseball player and spy who became an OSS operative in World War II gathering information about Germany's progress towards the development of an atomic bomb.